Convergence in fertility of South Africans and Mozambicans in rural South Africa, 1993–2009 - Michel Garenne; Stephen Tollman; Mark Collinson; Kathleen Kahn; Benn Sartorius; Latifat Ibisomi; Jill Williams (Taylor & Francis Group, 2013)
Background: Although there are significant numbers of people displaced by war in Africa, very little is known about long-term changes in the fertility of refugees. Refugees of the Mozambican civil war (1977–1992) settled in many neighbouring countries, including South Africa. A large number of Mozambican refugees settled within the Agincourt sub-district, underpinned by a Health and Socio-demographic Surveillance Site (AHDSS), established in 1992, and have remained there. The AHDSS data provide a unique opportunity to study changes in fertility over time and the role that the fertility of self-settled refugee populations plays in the overall fertility level of the host community, a highly relevant factor in many areas of sub-Saharan Africa. Objectives: To examine the change in fertility of former Mozambican self-settled refugees over a period of 16 years and to compare the overall fertility and fertility patterns of Mozambicans to host South Africans. Design: Prospective data from the AHDSS on births from 1993 to 2009 were used to compare fertility trends and patterns and to examine socio-economic factors that may be associated with fertility change. Results: There has been a sharp decline in fertility in the Mozambican population and convergence in fertility patterns of Mozambican and local South African women. The convergence of fertility patterns coincides with a convergence in other socio-economic factors. Conclusion: The fertility of Mozambicans has decreased significantly and Mozambicans are adopting the childbearing patterns of South African women. The decline in Mozambican fertility has occurred alongside socio-economic gains. There remains, however, high unemployment and endemic poverty in the area and fertility is not likely to decrease further without increased delivery of family planning to adolescents and increased education and job opportunities for women.